2021
DOI: 10.5194/acp-21-7429-2021
|View full text |Cite
|
Sign up to set email alerts
|

Air traffic and contrail changes over Europe during COVID-19: a model study

Abstract: Abstract. The strong reduction of air traffic during the COVID-19 pandemic provides a unique test case for the relationship between air traffic density, contrails, and their radiative forcing of climate change. Here, air traffic and contrail cirrus changes are quantified for a European domain for March to August 2020 and compared to the same period in 2019. Traffic data show a 72 % reduction in flight distance compared with 2019. This paper investigates the induced contrail changes in a model study. The contra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 83 publications
7
50
0
Order By: Relevance
“…Contrails are expected to reduce solar radiation reaching the Earth surface and to reduce outgoing longwave radiation. The mean changes induced by reduced air traffic in 2020 compared to 2019, computed in two model studies, were of the order of −0.1 to 0.5 Wm −2 over Europe (Gettelman et al, 2021;Schumann et al, 2021b), so at a magnitude comparable to the aerosol effects found in this study. We therefore plan to include contrail effects in a forthcoming study.…”
Section: Discussionsupporting
confidence: 66%
“…Contrails are expected to reduce solar radiation reaching the Earth surface and to reduce outgoing longwave radiation. The mean changes induced by reduced air traffic in 2020 compared to 2019, computed in two model studies, were of the order of −0.1 to 0.5 Wm −2 over Europe (Gettelman et al, 2021;Schumann et al, 2021b), so at a magnitude comparable to the aerosol effects found in this study. We therefore plan to include contrail effects in a forthcoming study.…”
Section: Discussionsupporting
confidence: 66%
“…The difference turns out large: 90 ± 50 mW m −2 for 2019 and 33 ± 35 mW m −2 for 2020 (which gives a mean of 62 ± 59 mW m −2 [18], incidentally close to the mean value given in [1]). [19] find for a large region in western Europe (20 • W to 20 • E, 35 • N to 60 • ), where air traffic (total flight distance above FL 180) was reduced due to COVID-19 by 72%, a strong reduction in contrail cover and radiative forcing. However, they state, as well, that the aviation-induced changes are relatively small (three to ten times smaller) compared to the natural variations seen in cirrus coverage and radiation fluxes at the top of the atmosphere.…”
Section: Introductionmentioning
confidence: 76%
“…Two recent examples of the huge variability induced on RF or ERF by weather variability are [18,19]. Gettelman et al use traffic data for 2006, scaled to 2019 traffic amounts.…”
Section: Introductionmentioning
confidence: 99%
“…The 2020 changes in air traffic likely resulted in reductions in contrail frequency (Schumann et al, 2021b). Aircraft contrails create linear condensation trails that can evolve and persist in supersaturated air as contrail cirrus.…”
Section: Introductionmentioning
confidence: 99%